Distribuição espaço - temporal e a pesca de siris (portunidae callinectes spp.) no estuário do rio mamanguape paraíba: um enfoque etnoecológico. - Ferreira, Emmanoela Nascimento (2010)
The research aimed to study the emic knowledge of swimming crabs (Portunidae - Callinectes spp.) fishermen, Tramataia community, located on the margins of Mamanguape River Estuary (MRE) from january 2009 to may 2010. The methodology encompassed qualitative methods: participant observation, free and semi-structured interviews and questionnaires. 30 community fishermen were interviewed. At least four captures techniques were identified: puçá e linha , trawl, siri de seco and siri de alagado . The swimming crabs are used for own consumption and marketing. According to the fishermen the capture techniques are determined by tide type. The sale of swimming crab meat is more usual in the region, but can also be marketed alive or frozen. Process stages of meat withdrawal consist: washing, cooking, meat removal, packaging, weighing and storage. The final product is marketed in the community, adjacent communities or free markets, and in some cases, by middlemen. Fishing in the community is characterized as artisanal and is performed both by women as men. The educational level of fishermen is low and the majority never completed elementary school. Because of the low profit of swimming crabs fishery, fishermen commonly exploit other resources. The results indicated that swimming crabs constitute an important basis of resource and survival for many families of Tramataia community, therefore this work can be useful to support future management plans to the region.